IMPLEMENTATION OF CORPORATE SOCIAL RESPONSIBILITY ON FINANCIAL PERFORMANCE OF MANUFACTURING COMPANIES IN INDONESIA - Antony Cang; Doni Putra Utama (JOURNAL OF APPLIED BUSINESS ADMINISTRATION, 2021)
This study is aimed to analyze the influence of Corporate Social Responsibility of financial performance at manufacturing companies listed on the Indonesia Stock Exchange. The sampling period studied was 2014 to 2018. The independent variable in this study was Corporate Social Responsibility which was assessed based on GRI indicators, namely Environmental Disclosure. The dependent variable of this study is financial performance measured by ROA, ROE, Revenues, and Tobin's Q, and the control variables used are Size and Age. The data used in this study were obtained from the company's 2014-2018 financial statements. Determination of the sample using purposive sampling technique in order to obtain a sample of 97 companies. Data analysis methods used are regression and partial t test. The results of this study are that Corporate Social Responsibility effected on financial performance measured by Revenues and Tobin’s Q while Corporate Social Responsibility does not affected on financial performance measured by ROA and ROE.